A Conditioned Exchange - Torisson, Fredrik (Footprint : Delft School of Design journal, 2019)
The emergence of financial institutions such as the exchanges or bourses of northern Europe in the sixteenth and the seventeenth centuries made possible the emergence of speculation in financial instruments. Speculation evolved into a game with its own logic, and the implied ethos of the speculator prioritised abstract notions and self-interest.This article investigates the relation between this ethos of speculation and architecture in this timeframe. During this period, the architecture of the exchanges transformed; what was a square with an inside at the outset gradually became an enclosed institution with representative façades toward the end of the period. The transition of the physical environment of exchange and the increasingly complex financial instruments interact, and this interaction is traced through a sequence of exchange-structures inspired by one another.The question explored is: what is the relationship between the emergence of an ethos of speculation and the architectural space of the exchange? This relationship can be discussed in terms of a different kind of conditioning that has less to do with industrialisation, but which could, in extension, form a starting point for discussions on architecture’s role in the formation and conditioning of homo œconomicus.